Analysis of oil price effect on economic growth of ASEAN net oil exporters - Karunanithi, Kriskkumar; Niaz Ahmad, Mohd Naseem (MDPI, 2019)
In this paper, the linear and nonlinear effects of oil price on growth for Association of Southeast Asian Nations (ASEAN)—3 net oil-exporting countries, namely Brunei, Malaysia and Vietnam, are investigated. The empirical analysis applies the augmented autoregressive distributed lag model (ARDL) bound test approach and the nonlinear autoregressive distributed lag model (NARDL) methodology over the period of 1979 to 2017. Evidence suggests that ignoring nonlinearities may lead to misleading results. Specifically, results reveal that the effect of oil price is asymmetric for the case of Brunei, while the effect oil price is deemed insignificant for the case of Malaysia and Vietnam, both linear and nonlinear model. Brunei’s high dependency on oil revenue makes it susceptible to negative oil price shock. This suggests that oil price still plays a significant role as the main driver of economic progress for Brunei.